SOME CONSIDERATIONS AND VIEWS ON THE STUDY OF THE HISTORY OF THE LIFE AND STATE ACTIVITIES OF AMIR TEMUR IN THE HISTORIOGRAPHY OF THE OTTOMAN EMPIRE (Scientific journal of the Fergana State University, 2024)
This article studies the life and state activities of Amir Temur in the historiography of the Ottoman Empire and highlights the stages of development. This study includes the reasons for the study of Sahibkiran by Ottoman-Turkish Timurid scholars and ideas for translating works produced during the Timurid period into Ottoman-Turkish.